Deiksis dalam Series Jodoh atau Bukan episode 1 - Aini Sudirman, Nurul; Fadillah, Nurul; Nurkholidha, Poppy; Ningsih, Rika (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2023)
Pragmatics is one of the sciences that studies deixis, deixis as a way to direct something that is directly related to the situation of speech. In this study, the researcher chose the Match or Not Series as the research subject. The reason the researcher researched the Matchmaking or Not Series episode 1 was because there were a lot of deixis the researcher found, namely persona deixis, space or place deixis, time deixis, and discourse deixis. The problem in this study is how the form of deixis in the matchmaking series or not episode 1. Data collection for this research was from 17 June 2023 to 24 June 2023, totaling 246 data. In this study the authors used qualitative research with descriptive analysis methods. The stages carried out in this study were the preparation of the writer to find data related to the research topic in the form of a theoretical companion book and watching the series Match or Not episode 1 then collect data, mark the part that contains deixis then save the data obtained. This study aims to focus on describing the deixis of persona, time, place contained in the Matchmaking or Not Series episode 1. The results of this study indicate that the deixis contained in the Matchmaking or Not Series episode 1, the researcher found that persona deixis is divided into the first persona deixis. singular, plural second person deixis, third person singular deixis, deiksis tempat dan deiksis waktu.